2018
DOI: 10.1007/s11682-017-9817-5
|View full text |Cite
|
Sign up to set email alerts
|

Congenital olfactory impairment is linked to cortical changes in prefrontal and limbic brain regions

Abstract: The human sense of smell is closely associated with morphological differences of the fronto-limbic system, specifically the piriform cortex and medial orbitofrontal cortex (mOFC). Still it is unclear whether cortical volume in the core olfactory areas and connected brain regions are shaped differently in individuals who suffer from lifelong olfactory deprivation relative to healthy normosmic individuals. To address this question, we examined if regional variations in gray matter volume were associated with sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 77 publications
4
36
4
Order By: Relevance
“…In line with previous studies, we could demonstrate that individuals with ICA have a significantly decreased olfactory sulcus depth, as compared to matched normosmic individuals (Yousem et al 1996;Abolmaali et al 2002;Huart et al 2011;Levy et al 2013;Karstensen et al 2018). The shallow olfactory sulcus depth in individuals with ICA is thought to be related to the complete lack of, or hypoplasia of, olfactory bulbs, often accompanied by small or absent olfactory tracts (Yousem et al 1996;Abolmaali et al 2002); structures located in the olfactory sulci.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies, we could demonstrate that individuals with ICA have a significantly decreased olfactory sulcus depth, as compared to matched normosmic individuals (Yousem et al 1996;Abolmaali et al 2002;Huart et al 2011;Levy et al 2013;Karstensen et al 2018). The shallow olfactory sulcus depth in individuals with ICA is thought to be related to the complete lack of, or hypoplasia of, olfactory bulbs, often accompanied by small or absent olfactory tracts (Yousem et al 1996;Abolmaali et al 2002); structures located in the olfactory sulci.…”
Section: Discussionsupporting
confidence: 90%
“…The cortical structural reorganization demonstrated by individuals with ICA were restricted to higher order olfactory (medial orbitofrontal) cortex, without indications of structural alterations in the primary olfactory (piriform) cortex. This lack of reorganization in primary sensory cortex is in disagreement with the literature on congenital visual sensory loss (Bridge et al 2009;Jiang et al 2009;Park et al 2009;Hasson et al 2016), as well as previous studies on individuals with congenital anosmia Karstensen et al 2018). Although the two previous studies investigating cortical morphology in individuals with congenital anosmia indicate increased cortical thickness and increased gray matter volume within the piriform cortex, their results are, however, unilateral and in opposite hemispheres.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…That olfactory loss is poorly studied is not surprising given that many think, erroneously, that the human sense of smell is a residual sense; however, humans have a better sense of smell than most animals (McGann 2017) and olfactory information is of importance for our wellbeing (Croy et al 2014). Congenital anosmia has been linked to morphological reorganization within the orbitofrontal cortex (Frasnelli et al 2013;Karstensen et al 2018;Peter et al 2019) including areas commonly referred to as secondary olfactory cortex (Lundström et al 2011), but, surprisingly, it has been suggested that no morphological alterations occur within primary olfactory cortex despite a life-long absence of olfactory input (Peter et al 2019). As of today, it is not known whether these morphological deviations (and suggested lack thereof) are reflected in functional neuroimaging data.…”
Section: Introductionmentioning
confidence: 99%
“…To date only a few studies have investigated the structural and functional alterations in CA. While reduced gray matter volume in olfactory related brain regions are found in acquired anosmia, CA is associated with increased gray matter volume in the primary olfactory area and the orbitofrontal cortex 14,15 . One recent study showed that CA exhibited audio-visual multisensory enhancement, which suggested a compensation for complete lack of olfactory input 16 .…”
mentioning
confidence: 99%